Portuguese Sorraia horse dynamics study with innovative technology: three natural gaits and strides - Faria, RAS (2022)
Portuguese native Sorraia horse is considered a primitive breed and ancestor of horses in Iberian Peninsula, where they inhabited since the Pleistocene. A closed mating system allowed to maintain the breed standard since its discovery, one century ago. The aim of this study was to characterize the dynamics of 6 Sorraia Stallions, considered very endangered (±300 living animals), using innovative technology equipment (EquiMoves). Three natural gaits, walk (W), trot (T) and canter (C), were evaluated using the variables stride duration (sD) in seconds (s), length (sL) in meters (m) and speed (sS) in kilometres per hours (km/h), considering the stride as a complete movement of the four limbs. Differences in LS mean between W, T and G within each variable were significant (P<0.05). The values of the variable sD were 1.16±0.10 s (W); 0.71±0.06 s (T) and 0.58±0.02 (C), with a decrease in stride duration from W to T by -41.8% and half the time from W to C (-100%) and from T to C was -18.3%. Values with opposite trends from W to T to C were observed in the variables sL and sS. Variable sL provided means of 1.44±0.06 m (W); 1.85±0.14 m (T) and 2.22±0.77 m (C), indicating increases in sL of 28.5% (W to T), 53.7% (W to C) and 19.9% between T and C. The values of the sS variable were equal to 4.39±0.18 km/h (W), 9.79±0.77 km/h (T) and 14.15±0.33 km/h (C), with increases from W to T of 223.0%, W to C of 322.3% and from T to C of 144.5%. 52 (W), 85 (T) and 103 (C) strides were observed per minute, and 74.4 (W), 156.3 (T) and 229.7 (C) meters were covered. To run 100 m (s) Sorraia horses need an average of 69 (W), 54 (T) and 45 (C) strides and take 80.0 (W), 38.3 (T) and 26.1 (C) seconds. Sorraia horses are considered ponies (1.46 m mean height at withers) and their height influences the variables evaluated and should not be compared with horses of different structures and sizes. Evaluation of variations within Walk, Trot and Canter traits should be observed in future studies.